Creta a Praeneste. Teseo e Arianna nel mosaico dei Pesci - Marcattili, Francesco (Römische Mitteilungen, 2024)
The contribution provides a detailed description and identification of the human figures depicted in the lower band of the so-called Fish Mosaic of Praeneste. The iconographic details permit the identification of the representation of Theseus and Ariadne in Crete. Theseus has just emerged from the sea, having visited his father Poseidon's palace in the abyss. Ariadne, characterised by the thread that was indispensable to the undertaking of the labyrinth, gazes absorbedly at Theseus from a cliff that juts out into the sea. The third partially preserved figure, a fisherman, is also linked by the author to the Cretan myth of Britomartis, a nymph "dearest to Artemis," who leapt into the sea from a cliff on Mount Dicte to evade the amorous advances of King Minos, and who was concealed/rescued precisely due to the efforts of the fishermen's nets.